FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PEDAGANG IKAN DI BEBERAPA PASAR TRADISIONAL DI MEULABOH - Yasrizal Yasrizal (JURNAL PERIKANAN TROPIS, 2017)
Fishery sub-sector is one sub-sector that has great potential to be developed. This study aims to determine how much influence the working capital, the number of fish sold, and the number of hours worked against the income of fish traders in Meulaboh. In this case hypothesized that the working capital variable, the number of fish sold, the number of working hours significantly and positively affect the income of fish traders in Meulaboh. Thus any increase that occurs in each variable will increase the income of fish traders in Meulaboh. Based on the results of the analysis, for the variable X1, H0 rejected and H1 accepted, it means working capital variables significantly affect pedapatan fish traders. For variables X2 and X3, H0 received H1 is rejected, meaning the number of fish sold and the number of working hours have no significant effect on the income of fish traders. Simultaneously, the working capital variable, the number of fish sold and the number of working hours significantly affect the merchant's income. 97.6% of changes in merchant income can be explained by changes in working capital variables, number of fish sold and number of working hours simultaneously. While the remaining 2.4% is explained by other variables that are not included as variables in the study. VIF values indicate that there is multicolinearity so it must be tested between independent variables. R12> R2 and R22> R2, it means multicollonierity.